Self-healing in epoxy thermoset polymer films triggered by UV light - Moniruzzaman, Monir; Christogianni, Paraskevi; Kister, Guillaume (Cranfield University, 2016)
Self-healing of damaged structures can occur in three processes: capsule-based healing, vascular healing and intrinsic healing of polymers. The latest concept has a tremendous potential to repair damaged polymers and composite structures. Until now self-healing of composite materials has been addressed using capsule based resin with an initiator that polymerises in the damaged region. In this study, self-healing behaviour of cured epoxy thermoset resins modified with an epoxy-functionalised photoresponsive azobenzene molecule has been addressed by UV light without the use of any resin capsules or other component that is not chemically joined with the composites. The study was executed by nanoindentation and atomic force microscopy (AFM). Artificially damaged thermoset films exhibited good self-healing behaviour under UV irradiation only. This effect is attributed to the intrinsic healing mechanism triggered by UV-induced trans→cis isomerization of the azobenzene chromophore which enables the damaged polymeric matrix to recover.
Keywords: Self-healing; Azobenzene; Nanoindentation; Resin